Transcriptional Control of Apical-Basal Polarity Regulators - Katja Rust (MDPI AG, 2021)
Cell polarity is essential for many functions of cells and tissues including the initial establishment and subsequent maintenance of epithelial tissues, asymmetric cell division, and morphogenetic movements. Cell polarity along the apical-basal axis is controlled by three protein complexes that interact with and co-regulate each other: The Par-, Crumbs-, and Scrib-complexes. The localization and activity of the components of these complexes is predominantly controlled by protein-protein interactions and protein phosphorylation status. Increasing evidence accumulates that, besides the regulation at the protein level, the precise expression control of polarity determinants contributes substantially to cell polarity regulation. Here we review how gene expression regulation influences processes that depend on the induction, maintenance, or abolishment of cell polarity with a special focus on epithelial to mesenchymal transition and asymmetric stem cell division. We conclude that gene expression control is an important and often neglected mechanism in the control of cell polarity.